PENGARUH PERUBAHAN DESAIN, PENGEMBANGAN TEHNOLOGI DAN PERFORMA MOTOR TERHADAP TINGKAT KEPUASAN PENGGUNA MOTORSPORT KAWASAKI NINJA 250 F1 DI KOTA BOGOR - Aditya Kurniawan; Samsuri Samsuri (Fakultas Ekonomi Universitas Djuanda, 2016)
This study aims to determine the development of products made by PT Kawasaki Motor Indonesia which includes design, technology development and product performance Kawasaki Ninja 250 FI and to determine the influence of changes in design, technology development and performance simultaneously and partially on consumer satisfaction users Kawasaki Ninja 250 FI. The population in this study is the Kawasaki Ninja 250 FI users belonging to the community Kawasaki Ninja. The sampling of 100 respondents was conducted by using probability sampling. This study was descriptive and verification. The collection of data through questionnaires and interview. Analisys data this research include multiple regression analysis, based on the results of multiple regression analysis of the F-test states that simultaneous factors design changes, technological development and performance motor influence on user satisfaction Kawasaki Ninja 250 FI. While the results of the t-test stating that the factor changes design, technology and performance motor partially affect the user satisfaction Kawasaki Ninja 250 FI.Keywords: Design Changes, Technology Development, Motor Performance, User Satisfaction